2008
DOI: 10.1128/jcm.01953-07
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Preclinical Detection of Sheeppox Virus by a Real-Time PCR Assay

Abstract: Sheeppox virus (SPPV) is a member of the Capripoxvirus (CaPV) genus of the Poxviridae family. Members of this genus, which also include goatpox and lumpy skin disease viruses, cause economically significant disease in sheep, goats, and cattle. A rapid diagnostic assay for CaPV would be useful for disease surveillance as well as for detection of CaPV in clinical samples and for outbreak management. Here we describe a fluorogenic probe hydrolysis (TaqMan) PCR assay designed for rapid detection of CaPV and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 25 publications
3
87
0
3
Order By: Relevance
“…Biopsy samples had the lowest Ct values which makes them the most suitable for testing. A number of real-time PCR methods for the detection of capripoxviruses have recently been described [3,11,18,22,23]. However, to our knowledge, until now no papers have been published describing TaqMan real Time PCR assays for the specifi c detection of the virulent fi eld strain of LSDV.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy samples had the lowest Ct values which makes them the most suitable for testing. A number of real-time PCR methods for the detection of capripoxviruses have recently been described [3,11,18,22,23]. However, to our knowledge, until now no papers have been published describing TaqMan real Time PCR assays for the specifi c detection of the virulent fi eld strain of LSDV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that TaqMan probe based duplex real-time PCR (drt-PCR) has been optimized with two different sets of primers and probes targeting the highly conserved DNA pol gene of capripox, sheeppox and orf virus genome. In comparison to real-time PCR for detection of orf virus, drt-PCR assay has proved to be more specific (100% diagnostic specificity) and highly sensitive (diagnostic sensitivity of 98.7%) (Balinsky et al, 2008;Balamurugan et al, 2009;Bora et al, 2011;Venkatesana et al, 2014a, b). Schmidt et al (2013) performed partial nucleotide sequencing and phylogenetic analysis of B2L gene of seventeen Brazilian orf viruses and concluded that discrete nucleotide changes in B2L gene may help in grouping orf viruses according to host species.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Detection of Capripoxvirus by PCR assay utilised genus specific primers and probe (Balinsky et al, 2008) and was performed on a 7900HT Fast Real-Time PCR System (Thermo Fisher Scientific, Waltham MA, USA) with standard ramping conditions. The sample analysed reacted positively for Capripoxvirus.…”
Section: Molecular Analysismentioning
confidence: 99%